A Conceptual Metaphors in Holocaust Literature: Pedagogical Implications for Thai Education - Supanchaikul, Pakthima (Scholar: Human Sciences, 2026)
This study aims to analyze (1) the metaphorical attributes inherent in the Holocaust literary genre, particularly in Heather Morris’s The Tattooist of Auschwitz and Antonio Iturbe’s The Librarian of Auschwitz, and (2) to compare the portrayal of Holocaust survivors’ life experiences in these works through the perspective of metaphorical elements. The study utilizes thematic analysis and metaphorical identification by interpreting the conventional metaphor from selected samples in chapters 19-24 of The Tattooist of Auschwitz and chapters 19-23 and 25-27 of The Librarian of Auschwitz. They are emphasizing the narrative structure from the climax to the denouement, situated in Auschwitz and perceived through the protagonist’s viewpoint. The results show symbolic themes of terror, suffering, life experience, survival, and death. The statistics show that both writers used metaphor differently. Morris described the protagonist’s life, tasks, and experiences, whereas Iturbe used the library, literature, and art to show life and survival. Moreover, the findings will yield pedagogical consequences for English language training in Thailand, primarily aimed at Grade 12 pupils. This research seeks to clarify the significance and roles of metaphorical elements relevant to the Thai context, employing the Holocaust genre as a case study to improve students’ empathetic and critical thinking skills.